2020
DOI: 10.3390/v12030329
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive Differential Splicing in Marek’s Disease Virus Can Discriminate CVI-988 Vaccine Strain from RB-1B Very Virulent Strain in Chicken Embryonic Fibroblasts

Abstract: Marek’s disease is a major scourge challenging poultry health worldwide. It is caused by the highly contagious Marek’s disease virus (MDV), an alphaherpesvirus. Here, we showed that, similar to other members of its Herpesviridae family, MDV also presents a complex landscape of splicing events, most of which are uncharacterised and/or not annotated. Quite strikingly, and although the biological relevance of this fact is unknown, we found that a number of viral splicing isoforms are strain-specific, despite the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Importantly, all three MDV gC proteins (gC, gC104, and gC145) are required for efficient horizontal transmission [22], but their expression at the mRNA or protein level had never been examined in epithelia skin cells. All three forms have been detected in RNA-Seq studies in infected cell cultures [16,22] and in B cells infected in vitro [17]. Here, we confirmed that both splice variants are expressed in epithelial skin cells with gC104 (MDV057.1) ~4-fold more abundant than gC145 (MDV057.2) and ~10-fold more abundant than the non-spliced transcript based on intron read depth (Fig 4A).…”
Section: Quantitative Analysis Of Mrna Splicing and Validation At The...supporting
confidence: 82%
“…Importantly, all three MDV gC proteins (gC, gC104, and gC145) are required for efficient horizontal transmission [22], but their expression at the mRNA or protein level had never been examined in epithelia skin cells. All three forms have been detected in RNA-Seq studies in infected cell cultures [16,22] and in B cells infected in vitro [17]. Here, we confirmed that both splice variants are expressed in epithelial skin cells with gC104 (MDV057.1) ~4-fold more abundant than gC145 (MDV057.2) and ~10-fold more abundant than the non-spliced transcript based on intron read depth (Fig 4A).…”
Section: Quantitative Analysis Of Mrna Splicing and Validation At The...supporting
confidence: 82%
“…So far, various vIL-8 splice variants have been identified, but it remained unknown whether each of the splice variants encodes a functional protein [ 12 ]. Recent comprehensive MDV transcriptome analyses identified a novel vIL-8 splice junction, which was detected at about 13–40-fold lower levels compared with previously published vIL-8 transcripts [ 6 , 12 , 13 ]. This new splice site was predicted to lead to a novel ORF that could potentially also splice with other transcripts through its splice acceptor site.…”
Section: Discussionmentioning
confidence: 87%
“…Thus, the complexity of herpesvirus gene expression is further increased by the fact that a substantial number of viral proteins are encoded from spliced transcripts and/or alternative splicing. Several spliced viral transcripts have been described for MDV in vivo and in vitro, e.g., for the meq , vIL-8, and gC genes [ 12 , 13 , 30 , 31 ]. Recent studies have indicated that a spliced transcript of vIL-8 and meq play a role in MDV pathogenesis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we hypothesized that the higher replication level of MDV/RB1B in the spleen at 21 and 28 dpi than that of MDV/CVI988 might be related to more transformed T cells in the spleen, which support the productive replication of MDV. It has been demonstrated that the respective specific cleavage patterns of MDV/CVI988 and MDV/RB1B after infecting host cells are important factors affecting viral pathogenicity and replication [ 29 , 30 ]. We present that the differential replication between MDV/CVI988 and MDV/RB1B in spleens and bursas may be related to the strain-specific splicing mode of MDV in different cells.…”
Section: Discussionmentioning
confidence: 99%